Experimental investigation into mechanical properties of coconut shell powder modified epoxy/ 3d E-glass composites - Nayak, Suhas Yeshwant; Shenoy B., Satish; Kini, Chandrakant R.; Hameed Sultan, Mohamed Thariq; Shahar, Farah Syazwani (Engineered Science Publisher, 2022)
The aim of this research work was to investigate the influence of resin modification with Coconut Shell Powder (CSP) on the tensile, flexural and impact properties of composites reinforced with 3D E-glass orthogonally woven fabric. The composites were fabricated using a combination of hand lay-up and press moulding techniques. Three different proportion of CSP namely, 0.5%, 1.5% and 3% by weight of resin were considered for modifying the epoxy resin. The properties of these composites were determined and compared with composites fabricated without coconut shell powder. Additionally, to ascertain the effect of dispersion technique on the mechanical properties of the composites, their tensile strengths were compared with composites fabricated with epoxy in which CSP was added to the resin and mixed mechanically. Improved mechanical properties were obtained for composites fabricated with modified resin and an increasing trend was observed with increase in proportion of CSP with the highest properties obtained for composites with 3% CSP content showing an increase of about 117%, 87% and 39% in tensile, flexural and impact strengths respectively over the composites without CSP. Tensile strengths of composites prepared by mechanical dispersion of CSP were lower than the resin modified composites having the same CSP content, showing a drop of about 53% and 25% thereby proving the efficacy of resin modification process. Scanning Electron Microscopy (SEM) was employed to analyse the characteristics of the CSP and to investigate the various failure modes.